2020
DOI: 10.1097/lbr.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of the Performance of 19-G Needle in Endobronchial Ultrasound-guided Transbronchial Aspiration for the Diagnosis and Testing of Molecular Markers in Lung Cancer

Abstract: Background: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has become the standard for diagnosis and staging of lung cancer. Historically, 21-and 22-G needles have been paired with EBUS. We evaluated the performance of EBUS-TBNA using a larger 19-G needle in the assessment of tumor tissue obtained and success of testing for molecular markers.Methods: We prospectively enrolled adult patients with lymphadenopathy concerning for metastatic lung cancer. Patients underwent diagnostic E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Studies analyzing PD‐L1 testing on lung carcinoma cytology specimens originated mostly from the USA, followed by publications arising from Italy, Canada, United Kingdom, China, Germany, Japan, India, Turkey and other countries. The Dako clone 22C3 was the most common clone analyzed on cytology specimens, followed by the Ventana SP263 clone 17–67 . The data collected included the clone type used in each study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies analyzing PD‐L1 testing on lung carcinoma cytology specimens originated mostly from the USA, followed by publications arising from Italy, Canada, United Kingdom, China, Germany, Japan, India, Turkey and other countries. The Dako clone 22C3 was the most common clone analyzed on cytology specimens, followed by the Ventana SP263 clone 17–67 . The data collected included the clone type used in each study.…”
Section: Resultsmentioning
confidence: 99%
“…There is no published evidence that needle size significantly affects sample adequacy for PD-L1 testing. 31,62 Although, a recent study by Hardy et al 76 showed that needle size can still affect adequate sample procurement. In this study, PD-L1 testing failures occurred in 3/5 (60%) 22G needle biopsies, 1/5 (20%) in 21G needle biopsies, and 2/39 (5.1%) in 19G needle biopsies (with a p value of .016).…”
Section: Specimen Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means the sample size is larger and cell blocks have enough tissue sample to diagnose lymphoma, sarcoidosis and other types of cancer (metastatic) [ 16 ]. The sample size of the 19G needle means more tissue and less cytology [ 17 , 18 ]. The issue remains for cases with high suspicion of lymphoma (Hodgkin and less for non-Hodgkin) and false negative results; however, the same issue remains for other cases of false negative results when we have necrotic samples.…”
Section: Discussionmentioning
confidence: 99%